Apple dwarfing rootstocks exhibit an imbalance in carbohydrate allocation and reduced cell growth and metabolism. (5th April 2017) - Foster, Toshi M; McAtee, Peter A; Waite, Chethi N; Boldingh, Helen L; McGhie, Tony K
Abstract: Apple dwarfing rootstocks cause earlier shoot termination and reduced root and shoot mass. To identify physiological factors responsible for rootstock-induced growth restriction, we compared vascular-enriched gene expression between two dwarfing rootstocks ('M27' and 'M9') and the vigorous rootstock 'M793' using RNA sequencing and quantitative reverse transcriptase PCR. Differentially expressed genes common to both dwarfing rootstocks belonged to five main biological processes: (1) primary metabolism, (2) cell wall synthesis and modification, (3) secondary metabolism, (4) hormone signalling and response and (5) redox homeostasis. Genes promoting the biosynthesis of amino acids, lipids and cell walls were downregulated in dwarfing rootstocks, whereas genes promoting the breakdown of these compounds were upregulated. The only exception to this trend was the upregulation of starch synthesis genes in dwarfing rootstocks. Non-structural carbohydrate analysis demonstrated that starch concentrations in 'M9' roots, stems and grafted 'Royal Gala' ('RG') scions were double that of equivalent tissues from 'RG' homo-grafted trees ('RG'/'RG'). Fructose and glucose concentrations were much lower in all three tissues of the 'RG'/'M9' trees. Together, these data indicate that dwarfing rootstocks are in a state of sugar depletion and reduced cellular activity despite having large starch reserves. Another significant finding was the over-accumulation of flavonoids and the downregulation of auxin influx transporters MdAUX1 and MdLAX2 in dwarfing rootstocks. We propose that both factors reduce polar auxin transport. The results of this study contribute novel information about the physiological state of dwarfing rootstocks. Abstract : Apples: Gene activity in dwarf rootstocks Dwarfing rootstocks used to grow smaller apple trees have a gene expression profile consistent with reduced cellular activity. Toshi Foster and colleagues from the New Zealand Institute for Plant & Food Research compared gene expression levels between two dwarfing rootstocks (the part of the plant onto which buds or shoots are grafted) and one full-size rootstock. They found that, compared to the full-size rootstock, both the dwarfing rootstocks showed reduced expression of genes involved in metabolism, hormone signaling and cell wall synthesis, and an increased expression of genes involved in breaking down amino acids, lipids and other compounds involved in cellular metabolism. Genes involved in starch synthesis were more active though, suggesting that dwarfing rootstocks keep apple trees small because they are in a continuous state of low energy usage despite having large starch reserves.